Analisis Perbandingan Kinerja Web Server Nginx dan Litespeed Menggunakan Httperf Dengan Sistem Operasi Debian - Cahyadi, Muhammad Leo; Setiawan, Herri; Mair, Zaid Romegar (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The correct web server used by a website system can ensure that the website can always run properly. Currently, many web servers can be used to run website systems; the two most popular ones are Nginx and Litespeed. This research compares the performance of the two web servers by configuring Nginx and Litespeed on the same server. Then, using httperf testing as a tool in this study. There are research parameters, namely how the performance is in managing Throughput, Connection, and Reply. The flow in comparing the two web servers is by serving user requests; the testing load is in the form of connection number and rate. These results are based on the response time needed to serve each web server client request; Nginx and Litespeed have strong performance in handling heavy web traffic. Nginx tends to be superior in handling client requests quickly, with an average of 0.33 ms, compared to the Litespeed web server, which has an average of 0.34 ms